2019
DOI: 10.18203/2349-2902.isj20195122
|View full text |Cite
|
Sign up to set email alerts
|

Plication: an innovative method of treating piles

Abstract: Background: The cause of haemorrhoids remains unknown. Factors contributing to haemorrhoids are constipation, prolonged squatting, pregnancy, aging, heredity, portal hypertension, abdominal tumour etc.Methods: This prospective study was carried out in department of surgery, M.K.C.G MCH, Berhampur, Odisha, India from 01st August 1995 to 31st July 2017. Patients from both sex and different age groups having haemorrhoids were included. Patients with piles secondary to anorectal tumours, prolapsed and thrombosed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…[12,16,14] Pattanayak S et al observed intra and postoperative bleeding occurred in (1.37%) in contrast to conventional method in which (13.4%) cases were having bleeding. [18] Agrawal S. et al, observed no postoperative bleeding. [17] Postoperative Retention of Urine Single case of postoperative retention of urine was noted in our series 80y /m who was also suffering from fistula in ano and bph.…”
Section: Postoperative Painmentioning
confidence: 96%
See 4 more Smart Citations
“…[12,16,14] Pattanayak S et al observed intra and postoperative bleeding occurred in (1.37%) in contrast to conventional method in which (13.4%) cases were having bleeding. [18] Agrawal S. et al, observed no postoperative bleeding. [17] Postoperative Retention of Urine Single case of postoperative retention of urine was noted in our series 80y /m who was also suffering from fistula in ano and bph.…”
Section: Postoperative Painmentioning
confidence: 96%
“…[17] Pattanayak S. et al observed in his study 484 patients (95.47%) got relieved from postoperative pain by 72 hours, whereas in conventional method only 178 patients (35.10%) got relief from postoperative pain by 72 hours. [18] Intra-Operative and Postoperative Bleeding…”
Section: Postoperative Painmentioning
confidence: 99%
See 3 more Smart Citations